Detection of maternal transmission of resistant Gram-negative bacteria in a Cambodian hospital setting - Chomkatekaew, Chalita; Thaipadungpanit, Janjira; Hearn, Pasco; Soeng, Sona; Pol, Sreymom; Neou, Leakhena; Hopkins, Jill; Turner, Paul; Batty, Elizabeth M. (Frontiers in Microbiology, 2023)
Infection with Extended-spectrum beta-lactamase -producing Enterobacterales (ESBL-E) is common in infants leading to increased intensive care unit admission and mortality, but the role of maternal transmission in colonisation of infants is unclear. Using paired isolates from 50 pairs of mothers and neonates admitted to a Cambodian hospital, we investigated antimicrobial resistance in Escherichia coli and Klebsiella pneumoniae using whole genome sequencing. We detected a wide variety of ESBL-E genes present in this population along with high levels of multidrug resistance. From 21 pairs where the same organism was present in both mother and neonate, we identified eight pairs with identical or near-identical isolates from both individuals suggestive of transmission at or around birth, including a pair with transmission of multiple strains. We found no evidence for transmission of plasmids only from mother to infant. This suggests vertical transmission outside hospitals as a common cause of ESBL-E colonisation in neonates.